How Does Situational Consumer Animosity Affect National Brand and Purchase Intentions in the US-China Trade War? - Lau, Albert D.; Li, Dacan; Gong, Yuanyuan; Somasundram, Sotheeswari; Lye, Ooi Chin (International Review of Management and Marketing, 2025)
Trump’s second presidency has initiated more intense global trade conflicts. This study investigates the impact of situational consumer animosity on national brand and consumers’ purchase intentions during the US-China trade war. This study centres on the USA as the focal country, smartphones as the product category, and Chinese consumers as the subject. Utilising the ABC Attitude Model, Theory of Reasoned Action, and the Revised Halo- Aggregate Effect Model as the theoretical framework. A quantitative research methodology was utilised to conduct an offline questionnaire survey with 310 customers in five major cities in China, employing covariance-based structural equation modelling (CB-SEM). The findings confirmed that the national brand exerts a significant influence, with the interrelation among the three components being Perceived Category Image → “Made In” Image → Perceived Country Image. This research enhanced the Revised Halo-Aggregate Effect Model by incorporating the Affective Country Image into the comprehensive national brand. This study is limited to China, with future studies potentially expanding this paradigm to the United States. This study advises the U.S. government to modify its trade war policies since it will diminish hostile nations’ perceptions of the U.S. national brand, subsequently influencing their purchase intentions for U.S. product brands.